Do low-cost digital tools allow measuring the cladode area? - Gomes, Henrique De Souza; Cordeiro Leita, Renan Matheus; Bezerra, Alan Cezar; Nogueira De Carvalho, Raphaell Aymá Alves; Nogueira De Carvalho, Maynar; Freire da Silva, Thieres George (Revista Brasileira de Engenharia de Biossistemas, 2024)
This study evaluated low-cost digital tools for estimating cladode area by mobile and fixed devices. We conducted the experiment at the Serra Talhada Academic Unit of the Federal Rural University of Pernambuco with pear cactus (Nopalea cochenillifera Salm-Dyck and Opuntia stricta (Haw.)). In this sense, we used four software to measure the cladode area: LAFore (fixed device), ImageJ (fixed device), Easy Leaf App (mobile device), and Petiole App (mobile device). We considered the LAFore software as a reference and used the following statistical parameters: linear regression, correlation coefficient (r), Willmott index (d), confidence index (c), and standard error of estimate (SEE). The software on fixed devices (ImageJ and LAFore) showed similar results, with performance considered excellent, and the Easy Leaf App showed a very good performance among mobile devices.